2000
DOI: 10.1111/j.1469-7998.2000.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Social structure of a polygynous tent‐making bat,Cynopterus sphinx(Megachiroptera)

Abstract: The social structure of an Old World tent‐making bat Cynopterus sphinx (Megachiroptera), was investigated in western India. A combination of census and mark–recapture data over 2 years (1996–98) was used to infer the form of the mating system, compositional stability of social groups and mode of new social group formation. The breeding population of C. sphinx was subdivided into diurnal roosting colonies, each of which contained one to five discrete roosting groups and often one or more solitary bats in adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 50 publications
0
39
0
2
Order By: Relevance
“…In contrast, male L. silvicolum with harems were heavier than unsuccessful males throughout the year. We cannot exclude the possibility that this difference in physical condition is an age effect as in other species (Kunz et al 1983;Storz et al 2000). Regardless of age, males that did monopolize a nest, but did not manage to attract females, were of intermediate mass.…”
Section: Male Point Of Viewmentioning
confidence: 88%
“…In contrast, male L. silvicolum with harems were heavier than unsuccessful males throughout the year. We cannot exclude the possibility that this difference in physical condition is an age effect as in other species (Kunz et al 1983;Storz et al 2000). Regardless of age, males that did monopolize a nest, but did not manage to attract females, were of intermediate mass.…”
Section: Male Point Of Viewmentioning
confidence: 88%
“…Studies in other fruit bats have identified heterogeneity in age composition among roosts. For example, there are indications that some harems in Cynopterus sphinx are founded by nulliparous females of the same age cohort (Storz et al, 2000).…”
Section: Seasonal Variation In Roost Location Size and Compositionmentioning
confidence: 99%
“…Available evidence suggests that the degree of polygyny may be subject to a considerable degree of geographic variation in C. sphinx . Information on the mode of social organization and mating system is available for Pune (northern locality; Storz et al, 2000b) and Palayamkottai (southern locality; Storz et al, 2000a). In both localities, the clustering of breeding females in confined roosting spaces facilitates a male mating strategy of resource defense polygyny (Storz et al, 2000a,b).…”
Section: Geographic Variation In Sexual Dimorphismmentioning
confidence: 99%
“…In addition to fecundity selection on females, sexual selection on males may also be an important driving force in the evolution of sexual dimorphism in bats. If body size influences suc-cess in territory acquisition and/or mating access to receptive females, the opportunity for sexual selection on male size is expected to be greatest in species characterized by highly polygynous mating systems (e.g., McCracken & Bradbury, 1981;Storz et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%